REAKSI ASIMETRI ATAS SINYAL BELI DAN JUAL ANALISIS TEKNIS: PENGUJIAN BIAS KONFIRMASI SEBELUM PENGUMUMAN LABA - Dedhy Sulistiawan (Jurnal Keuangan dan Perbankan, 2015)
The main purpose of this study is to examine asymmetry reaction on buying and selling technical analysis signal before earnings announcements. Behavioral finance theory is used in explaining why confirmation bias stimulates asymmetry reaction to stock return. To support that idea, this article uses technical analysis as an important feature in testing confirmation bias. Using Indonesian stock market data, the results show that technical analysis signal produce higher return in buying signal than selling signal. Investors give different attention in anticipating technical analysis signal around earnings announcements. This finding contributes to behavioral finance and technical analysis studies.